THE EFFECT OF LIQUIDITY, LEVERAGE, CAPITAL, EFFICIENCY, AND ASSET QUALITY ON ISLAMIC BANKS PROFITABILITY IN ASIA - Lina Kurniawati; Guntur Kusuma Wardana; Muhammad Riza Hafizi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
Sharia banking in Asia has experienced rapid asset growth and has become a major contributor to the global Islamic finance industry. However, this asset growth has not always been accompanied by stable profitability due to high operating costs and financing risks. This study aims to examine the FDR, DAR, CAR, CIR, and NPF on ROA in Islamic banking in Asia. This study uses a descriptive quantitative approach with panel data regression analysis. The results show that, partially, the variables FDR, DAR, and CAR do not have a significant effect on ROA, while the variables CIR and NPF have a significant negative effect on ROA in Islamic banks in Asia. Simultaneously, all independent variables have a significant effect on ROA in Islamic banks in Asia. This study explains that asset efficiency and quality are important factors that affect the profitability of Islamic banking in Asia. The implication of this study is the need to strengthen financing risk management and improve operational efficiency to maintain the financial performance of Islamic banking.